Strategies for Mainstreaming Edible Cities with Focus on the City of Lincoln: A Critical Cross-Case Study Analysis of Community Growing Groups in the UK - Hannah Williams; Amira Elnokaly (Urban Science)
The socio-political climate in the UK, compounded by government austerity measures, has intensified the cost-of-living crisis, significantly impacting the affordability of the food supply chain. This has led to an increasing disconnect from healthy dietary practices and has contributed to declines in mental and physical wellbeing. This paper examines the role of edible city (EC) initiatives in addressing these challenges by enhancing food security, fostering social resilience and supporting community wellbeing. The aim of this research is to understand the tangible links between EC mechanisms and how they align with local, cultural and geographical perspectives. Focusing on the City of Lincoln, UK, this study aims to develop a contextualised EC framework that is culturally and geographically relevant and aligns with global goals for sustainable urban development as outlined in the United Nation’s Sustainable Development Goal 11 (SDG11), promoting inclusive, environmentally safe and economically viable communities. Utilising a mixed methods approach, this research combines qualitative interviews and a critical cross-case analysis of four community growing groups in the UK, alongside quantitative socio-demographic data analysis. The findings reveal that successful EC initiatives adapt to their environment and socio-cultural conditions and highlight the importance of EC diversification for long-term sustainability. Four core themes emerged across the case studies: (1) social prescribing, (2) social capital (3) knowledge sharing and (4) social value. These findings inform the creation of a novel flexible EC framework, Lincoln, providing actionable insights and policy recommendations to support sustainable urban regeneration and enhance community resilience. This research contributes transferable knowledge to inform EC strategies across diverse global urban contexts, promoting a pathway toward resilient and socially cohesive urban environments.